Inspeção técnica de pulverizadores agrícolas conforme a norma ISO 16122 - Martini, Alfran Tellechea (2017)
The primary sector development by the expansion of cultivation areas and the increase in the productive indices promoted the increase of pesticide uses. That reflect in problems related to application inefficiency, making a important point to be studied mainly related to spray precision. Taking account the necessity in reduced the environmental contamination and increase the pesticides application quality, this work aimed conduct a project for agricultural sprayers inspection based on the norm ISO 16122 in the first time in Brazil. For this, a team of Laboratório de Agrotecnologia da Universidade Federal de Santa Maria moved in nine towns in central and west frontier of Rio Grande do Sul state. Sprayers coupled to the traction bars of tractors and to hydraulic system of three points, totaling 56 sprayers were evaluated using the ISO 16122 standard any its parts. Based on the obtained results, was possible observed that the state of use and conservation of agricultural sprayers inspected were considered serious because 67.85% were discontent with the used methodology, 26.79% showed partial compliance and only 5.35% were classified in accordance with the used metodology. The most serious problems were related to the operator security and environmental contamination that showed 41.07% of sprayers without the cardan shaft and 33.93% of sprayers did not have belts and pulleys. In addition, 46.43% of the sprayers evaluated showed static leaks, 87.50% showed dynamic leaks. Even in 71.43% did not have clean water tank to washing rigid packaging. Considering the most common problems related to application activity, was verified that in 64.29% the pressure gauge accuracy was considered grave and in 73.21% the distribution of the spray bar was considered grave too. This is related mainly to the high nozzle spacing error and due the spray nozzle wear that affect the equipment application volume in 76.79%. Besides the mentioned items, was also observed that 69.64% of inspection sprayers the PTO rotation was lower than recommended. Therefore, it can be concluded that there is a need for agricultural sprayer inspections to become mandatory in Brazil.